2021
DOI: 10.1007/s15010-021-01735-1
|View full text |Cite|
|
Sign up to set email alerts
|

Epidemiology and in vitro activity of ceftazidime–avibactam, meropenem–vaborbactam, imipenem–relebactam, eravacycline, plazomicin, and comparators against Greek carbapenemase-producing Klebsiella pneumoniae isolates

Abstract: Background The increase in carbapenem-resistant Klebsiella pneumoniae (CRKP) infections is of great concern because of limited treatment options. New antimicrobials were recently approved for clinical therapy. This study evaluated the epidemiology of carbapenemase-producing K. pneumoniae isolates collected at a Greek university hospital during 2017-2020, and their susceptibilities to ceftazidime-avibactam (CAZ/AVI), meropenem-vaborbactam (M/V), imipenem-relebactam (I/R), eravacycline, plazomicin, and comparato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 37 publications
3
7
2
Order By: Relevance
“…However, the emergence of some resistance also reminds the need to monitor antimicrobial activity and strengthen management. 40 Moreover, for the efficacy evaluation of some “classical” antibiotics, a meta-analysis showed that the resistance rates of CRKP to colistin, polymyxin B, gentamicin and fosfomycin were 31.1%, 9.8%, 35.7% and 47.3%, respectively. 41 That, in addition to newer agents, some relatively “old” drugs still retain a certain (or even good) effect on CRKP infections.…”
Section: Discussionmentioning
confidence: 99%
“…However, the emergence of some resistance also reminds the need to monitor antimicrobial activity and strengthen management. 40 Moreover, for the efficacy evaluation of some “classical” antibiotics, a meta-analysis showed that the resistance rates of CRKP to colistin, polymyxin B, gentamicin and fosfomycin were 31.1%, 9.8%, 35.7% and 47.3%, respectively. 41 That, in addition to newer agents, some relatively “old” drugs still retain a certain (or even good) effect on CRKP infections.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, plazomicin maintains its activity against many MDR Enterobacteriaceae and was approved in 2018 by the FDA for the treatment of complicated urinary tract infections related to E. coli, K. pneumoniae, Enterobacter cloacae, and Proteus mirabilis (Serio et al, 2019). Several studies in vitro have confirmed its antibacterial activity on MBL-producing Enterobacteriaceae at a concentration of 0.75-2 µg/ml (Serio et al, 2019;Johnston et al, 2021;Maraki et al, 2022). No study on its antibacterial activity against MBL-producing P. aeruginosa or A. baumannii was found.…”
Section: Plazomicinmentioning
confidence: 99%
“…Recently, eravacycline has been approved for use in complicated intra-abdominal infections, including infections caused by MBL producers (Solomkin et al, 2019 ). Eravacycline at 1–4 μg/ml exerts potent antibacterial activity on all or most of the tested Enterobacteriaceae strains producing MBLs (Zhang et al, 2016 ; Johnston et al, 2020 ; Maraki et al, 2022 ). However, no relevant studies have been conducted to test its antibacterial activity in MBL-producing P. aeruginosa or A. baumannii thus far.…”
Section: Novel Antibiotics and β-Lactamase Inhibitors In Preclinical ...mentioning
confidence: 99%
“…Emergence of resistance among enterococci is also possible due to a combination of rpsJ mutations and horizontal transfer of tet genes ( 5 ). Indeed, the emergence of resistance to promising agents such as ERV and plazomicin highlights the need for continuous surveillance and application of enhanced antimicrobial stewardship ( 11 ).…”
Section: Introductionmentioning
confidence: 99%